Behavioral Counseling Theory using Imitation Techniques to Improve the Character of Middle School Students - Putri Naziah; I Ketut Dharsana; Ni Ketut Suarni (Bisma The Journal of Counseling, 2025)
The decline in moral character among junior secondary school students has become an increasingly prominent educational issue in line with social changes and technological advancement, necessitating planned and sustained interventions to reconstruct students’ positive behavior. This study aims to examine the effectiveness of a behavioral counseling approach using modeling techniques in improving students’ moral character. The study employed an experimental approach with an experimental group and a control group design. The research subjects consisted of two classes, serving as the treatment group and the comparison group. The intervention was administered to the experimental group through a behavioral counseling approach using modeling techniques with symbolic models in a classical setting. Data were collected using a moral character questionnaire based on a rating scale. Instrument validity was examined through content validity and construct validity, while reliability was tested using an internal consistency reliability coefficient with the assistance of statistical software. Data analysis was conducted using a mean difference test to identify differences between groups. The results revealed a significant difference between the treatment group and the comparison group, indicating that the behavioral counseling approach with modeling techniques had a strong effect on improving students’ moral character. The findings confirm that the behavioral counseling approach with modeling techniques is effective as a guidance and counseling service strategy to strengthen students’ character. The implications of this study support the integration of behavioral counseling approaches into character development programs in educational settings.